The seven deadly virtues : eighteen conservative writers on why the virtuous life is funny as hell - Last, Jonathan V., 1974- (Conshohocken, PA. Templeton Press, 2014)
Here are the virtues everyone was taught in Sunday school but have totally forgotten about. Eighteen conservative writers offer their insights on why both the classical and everyday virtues are still important... and why readers shouldn't get carried away with them
Keywords: Conduct of life -- Humor; Virtues -- Humor